Thorax ultrasound in the management of pediatric pneumonias complicated with empyema - Pinotti, Karin F.; Ribeiro, Sergio Marrone [UNESP]; Maria Cataneo, Antonio Jose (Springer, 2006)
The aim of this work is to prospectively study the value of thoracic ultrasound (US) before pleural drainage in children with parapneumonic effusion (PPE). All children hospitalized for PPE, identified by thoracic radiography, underwent US to assess pleural loculation, echogenicity, and pleural fluid quantity. From August 2001 to July 2003, 52 children were examined. US was performed on 48 of these children, of whom 35 received chest tube drainage and 13 only received clinical treatment. US identified 38 patients with free flowing and 10 with loculated pleural fluid. About 25 of the free flowing (65.8%) and 10 (100%) of the loculated patients received chest tube drainage. Echogenicity was anechoic in 13, echoic without septations in 17 and echoic with septations in 18. Chest tube drainage was required in 6 anechoic (46.15%), 14 echoic without septations (82.35%), and 15 echoic with septations (83.33%). Quantity of fluid estimated by US varied from 20 to 860 ml. Effusion volume was higher in patients that were echoic with septations and loculated effusions. Pleural glucose and pH were lower, and LDH was higher in loculated PPE patients. In conclusion, US is an auxiliary exam for determining whether thoracic drainage is needed in parapneumonic effusion; loculated or echoic effusion should be drained, and free anechoic fluid needs further investigation.
Keywords: pneumonia; ultrasound; empyema; complications; pleural